A review of single electrode triboelectric nanogenerators - Akram, Wasim; Chen, Qian; Xia, Guangbo; Fang, Jian (Nano energy, 2023)
Triboelectric nanogenerators (TENGs) play a prominent role in steadily developing the Internet of Things (IoT) and the Fourth Industrial Revolution (fusion of progression in IoT, artificial intelligence, robotics, and related technologies) by shaping ambiance mechanical energy into electricity. Single electrode mode (SE-mode) of the TENGs has the simplest configuration where the sole electrode is grounded, and the contact separation or sliding of triboelectric surfaces establishes current flow between ground and electrode. Easily operatable, having attached electrode to only one triboelectric surface, prefer them over the paired electrode TENGs, making it easy for them to be integrated into other devices for self-powered sensing. This review provides a summary of the recently developed film and textile-based single electrode triboelectric nanogenerators (SE-TENGs). Their construction, applications, output performances, performance enhancing approaches with fabrication techniques, and measured durabilities are outlined. Film-based SE-TENGs are briefed on the base of metal electrodes, 1D and 2D nanomaterials-based, conductive materials encapsulated in elastic matrices, and conductive hydrogels, while textile-based SE-TENGs are categorized into knitting-based, weaving-based, and conductive fabrics as electrodes for SE-TENGs. Finally, existing challenges and future developments in SE-TENGs are discussed. [Display omitted] •Principle, construction, and power generation of single electrode TENGs (SE-TENGs).•Various applications of film and textile-based SE-TENGs.•Strategies for improving the output performance of SE-TENGs.•Challenges and future research directions in SE-TENGs have been proposed.